The Influenced of ESG Environmental Performance on Financial Performance: A Study of Indonesian Publicly Listed Companies - Muh. Alif Rumansyah, A.; Anny Nainggolan, Yunieta (Journal of Accounting and Finance Management, 2025)
Environmental, Social, and Governance (ESG) factors have become crucial in corporate strategy and financial decision-making. This study examines the impact of environmental performance on financial performance—measured by Return on Assets (ROA) and Return on Equity (ROE)—of publicly listed companies in Indonesia. Using panel data regression, the research analyzes companies in the IDX ESG Leaders, SRI-KEHATI, and ESGQ-KEHATI indices from 2019 to 2023. Environmental performance indicators include emissions, energy consumption, water usage, and waste management, with firm size, leverage, and governance characteristics as control variables. The findings indicate that environmental performance influences financial performance, though its effects vary across indicators. Some sustainability practices improve financial outcomes, while others incur short-term costs. The study highlights the risk of greenwashing, emphasizing the need for standardized ESG reporting. These insights are valuable for corporate decision-makers, investors, and regulators to develop effective ESG strategies that balance sustainability with financial growth.